The Perception of English Study Program Students on Using Google Translate in Writing Assignments - Daeng, Siti Monalisa Maruddani Yusuf; Eliwarti, Eliwarti; Syarfi, Syarfi (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
Translation is an activity in which students learn and transfer meaning from English to Indonesian, or vice versa. This research aims at determining the perception of English study program students towards the use of Google Translate for writing assignments. This research was a mixed-method research. The researchers used interview and questionnaire as the instruments of this research. The data obtained from interview was analyzed qualitatively, and the data obtained from questionnaire was analyzed quantitatively using Statistical Package for the Social Sciences (SPSS) software and Microsoft Excel. The result showed that 62.6% of English students had a positive opinion of Google Translate when using it for writing projects. The average of every item was used to determine this value. Item 13 displayed 59% of the data, which was the middle figure or percentage. The item with the highest score, item 3, received a 71%. The perception on the use of Google Translate among fourth-semester English students at Riau University in writing assignments was positive, despite participants stating that the writing process with Google Translate was only to expand vocabulary. Students realized Google Translate can help them in writing. At last, the majority of English students utilize Google Translate to increase their vocabulary.